2016
DOI: 10.1097/md.0000000000005624
|View full text |Cite
|
Sign up to set email alerts
|

Revision surgery after pregnancy in a patient with congenital kyphoscoliosis

Abstract: Rationale:Rod breakage during pregnancy and delivery has never been described in a patient who has undergone surgery for congenital scoliosis (CS). Here, we present an unusual but significant case of revision surgery.Patient concerns:A 29-year-old woman presented with low back pain during pregnancy after posterior osteotomy, correction and fusion at T9 to L5 for CS. Radiographs during follow-up, 4 months after the patient gave birth, demonstrated rod breakage.Diagnoses:Rod breakage after orthopaedic surgery of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
(18 reference statements)
0
1
0
Order By: Relevance
“…The physical burden that a fetus places on the spine of the mother with underlying scoliosis might lead to curve progression and – as a consequence - rod migration [ 17 ]. Li et al [ 19 ] described a case of revision surgery after pregnancy (4 months after the patient gave birth) in a patient with congenital kyphoscoliosis, in who the spinal rod was broken. The authors reported that the weight gain of pregnancy was the most likely reason for the rod breakage.…”
Section: Discussionmentioning
confidence: 99%
“…The physical burden that a fetus places on the spine of the mother with underlying scoliosis might lead to curve progression and – as a consequence - rod migration [ 17 ]. Li et al [ 19 ] described a case of revision surgery after pregnancy (4 months after the patient gave birth) in a patient with congenital kyphoscoliosis, in who the spinal rod was broken. The authors reported that the weight gain of pregnancy was the most likely reason for the rod breakage.…”
Section: Discussionmentioning
confidence: 99%